EVACUATION OF THE POPULATION IN THE EVENT OF FLOODING AND THREAT - М.Б. Арипходжаева; Хакимов Озодбек Хамиджонович (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation: Humanity, entering the XXI century, can consider and analyze the impact of various disasters and other problems of the past centuries, the article presents various  ways  to  eliminate  all  types  of  emergencies  and  evacuate  the  population. Evacuation is considered completed when all the population to be evacuated will be removed from the boundaries of the zone of action of the damaging factors of the source of emergency situations to safe areas. When forming this work, the requirements of  the  governing  and  regulatory  documents  in  force  during  the  evacuation  of  the population were taken into account.